Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1987
DOI: 10.1111/j.1442-9993.1987.tb00945.x
|View full text |Cite
|
Sign up to set email alerts
|

The occurrence and diet of fishes in a tidal inlet to a saltmarsh in southern Moreton Bay, Queensland

Abstract: The fishes occurring in the main tidal inlet to a typical saltmarsh situated in southern Moreton Bay were studied from January to December 1984. The aim of the study was to determine the type of fishes and their feeding habits within the inlet, particularly for species of economic importance. Sampling was conducted at night on the full and new moon phases, and during the day on the full moon phase. A total of 19 species were recorded from the inlet, of which 11 are of economic importance. Six species were cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(52 citation statements)
references
References 22 publications
1
51
0
Order By: Relevance
“…These dominant species were from the families Ambassidae, Atherinidae, Gobiidae and Sparidae. Australian studies that have sampled saltmarsh creeks also have reported numerical dominance by estuarine species (Gibbs 1986, Morton et al 1987, Davis 1988). Similar observations have been reported for saltmarsh flats and creeks in the northern hemisphere (Subrahmanyam & Drake 1975, Shenker & Dean 1979, Cattrijsse et al 1994.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These dominant species were from the families Ambassidae, Atherinidae, Gobiidae and Sparidae. Australian studies that have sampled saltmarsh creeks also have reported numerical dominance by estuarine species (Gibbs 1986, Morton et al 1987, Davis 1988). Similar observations have been reported for saltmarsh flats and creeks in the northern hemisphere (Subrahmanyam & Drake 1975, Shenker & Dean 1979, Cattrijsse et al 1994.…”
Section: Discussionmentioning
confidence: 99%
“…Initial work in Australia was done in single tidal creeks that drained the saltmarsh flats (Gibbs 1986, Morton et al 1987, Davis 1988, and in semi-permanent pools that remain on the flats after the tide has receded (Gibbs 1986, Davis 1988, Morton et al 1988. None of these studies, however, investigated whether fish actually occurred on the intertidal saltmarsh flats.…”
Section: Introductionmentioning
confidence: 99%
“…Strategies to control mosquito populations include habitat modification to maintain or restore tidal flooding, chemical control using non-specific chemicals to limit the abundance of adult mosquitoes, and biological control facilitated by the consumption of larvae by fish and shrimp (Morris et al 2002;Morton et al 1988;Morton et al 1987). Pseudomugil signifer, a small fish commonly found in saltmarsh, was found in laboratory studies to prey on mosquito larvae but was satiated at moderate densities (Willems et al 2005).…”
Section: Carbon and Aquatic Foodwebsmentioning
confidence: 99%
“…Many studies have demonstrated the high proportion of temporary resident fish occurring as juveniles in shallow tidal wetlands containing seagrass, mangroves or salt marsh (Morton et al 1987;Bell and Pollard 1989;Ferrell and Bell 1991;West and King 1996;Gray et al 1996Gray et al , 1998Hannan and Williams 1998). Many of these estuarine fishes move between habitats on seasonal and/or inter annual cycles and an appropriate surrogate for the functional equivalence and sustainability of the modified habitat is the utilisation of the area by fish and invertebrates in a similar way to external reference sites and estuaries.…”
Section: Urban Environments: the New Habitatmentioning
confidence: 99%